2022
DOI: 10.1038/s41531-022-00380-1
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson-causing mutations in LRRK2 impair the physiological tetramerization of endogenous α-synuclein in human neurons

Abstract: α-Synuclein (αSyn) aggregation in Lewy bodies and neurites defines both familial and ‘sporadic’ Parkinson’s disease. We previously identified α-helically folded αSyn tetramers, in addition to the long-known unfolded monomers, in normal cells. PD-causing αSyn mutations decrease the tetramer:monomer (T:M) ratio, associated with αSyn hyperphosphorylation and cytotoxicity in neurons and a motor syndrome of tremor and gait deficits in transgenic mice that responds in part to L-DOPA. Here, we asked whether LRRK2 mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 82 publications
1
7
0
Order By: Relevance
“…We differentiated these iPSCs into excitatory glutamatergic neurons using tetracycline-inducible expression of NGN2 (Pantazis et al, 2022), and live-imaged EGFP-LC3-labeled AV transport in the mid-axon at DIV21 (Figure 1A; Video S1). NGN2-induced neurons (iNeurons) express LRRK2 (Bieri et al, 2019; Boecker et al, 2021; Fonseca-Ornelas et al, 2022) and have been used to study the effect of LRRK2 -p.G2019S on axonal AV dynamics (Boecker et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…We differentiated these iPSCs into excitatory glutamatergic neurons using tetracycline-inducible expression of NGN2 (Pantazis et al, 2022), and live-imaged EGFP-LC3-labeled AV transport in the mid-axon at DIV21 (Figure 1A; Video S1). NGN2-induced neurons (iNeurons) express LRRK2 (Bieri et al, 2019; Boecker et al, 2021; Fonseca-Ornelas et al, 2022) and have been used to study the effect of LRRK2 -p.G2019S on axonal AV dynamics (Boecker et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that tetramers undergo destabilization of their helically folded conformation prior to α-Syn aggregation into abnormal oligomeric and fibrillar assemblies [ 16 , 17 ]. Although the importance of the tetrameric structure of α-Syn in the physiological condition is debated in favor of the more common unstructured monomeric form [ 18 ], there is evidence that this structure is sensitive to the presence of various mutations associated with PD [ 19 , 20 ]. Numerous investigations have connected the physiological activity of α-Syn in monomeric forms to synaptic functionality [ 21 , 22 ], although there are still no conclusive results about its physiological function, while the pathological events associated with α-Syn are almost exclusively linked to its polymeric forms.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research indicates that WT α-Syn exists in a stable tetrameric form, while missense mutations tend to form monomeric structures that trigger pathological aggregation . Moreover, the disruption or impairment of α-Syn multimerization leads to an excess of monomers at vesicle membranes, resulting in round cytoplasmic inclusions and indicating pathological consequences. Our results suggest that CAE disrupts the α-Syn oligomeric equilibrium, favoring monomers with hindrance in homogeneous regions and causing oligomer formation in punctate distributions in SH-SY5Y cells. This finding highlights the potential link between CAE and α-Syn pathology.…”
Section: Discussionmentioning
confidence: 97%